2018
DOI: 10.22437/ppd.v6i1.5176
|View full text |Cite
|
Sign up to set email alerts
|

Competences of municipalities in waste economy

Abstract: Healthy living environment is basic factor of modern society, orientated to the sustainable development. Waste economy presents activity, orientated to the avoiding and limitation of waste rising and decreasing of their negative impacts to the living environment. Slovak Republic gives to the tasks of living environment intensive attention from the view of legislative and economic measurements. Every year financial means are invested to the protection of living environment and there is created database and syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Results of this article have shown that policies must be implemented also on the regional level, because in Slovakia and probably in other countries, the differences between regions in waste treatment are significant. Waste management fees are set either by municipalities or by companies that further process waste, but these fees are different, with a very low separation rate in Slovakia-only around 16% and improving slowly [37]. Another problem in Slovakia is the low level of industry involvement in environmental activities, the positive news is the industry's willingness to support eco-innovation [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of this article have shown that policies must be implemented also on the regional level, because in Slovakia and probably in other countries, the differences between regions in waste treatment are significant. Waste management fees are set either by municipalities or by companies that further process waste, but these fees are different, with a very low separation rate in Slovakia-only around 16% and improving slowly [37]. Another problem in Slovakia is the low level of industry involvement in environmental activities, the positive news is the industry's willingness to support eco-innovation [38].…”
Section: Discussionmentioning
confidence: 99%
“…By synthesizing the results of the above-mentioned statistical analysis, we came to the conclusion that the implementation of the circular model in order to reduce interregional disparities in the management of produced municipal waste with an emphasis on waste recovery (both material and energy), which determines the integration of the principles of the circular economy should follow a clearly defined model of municipal waste recovery management, as shown in Figure 9 below. 16% and improving slowly [37]. Another problem in Slovakia is the low level of industry involvement in environmental activities, the positive news is the industry's willingness to support eco-innovation [38].…”
Section: Discussionmentioning
confidence: 99%